Fault Interruption Scheme for HVDC System Using SiC-MESFET and VCB Based Hybrid Circuit Breaker - Waheed A. Khan (IEEE, 2021)
As high voltage DC power system is gaining popularity, power electronic switching devices are becoming increasingly advanced to overcome problems of timely fault isolation. In this context, hybrid DC circuit breakers (DCHCBs), especially, together with wideband gap-based semiconductor devices, play a crucial role to tackle the current and voltage at high power and frequency. In this paper, a hybrid DC circuit breaker is designed leading to development of a fault interruption scheme for HVDC power system, as in HVDC system, fault interruption is considered more critical compared to the conventional high voltage AC (HVAC) power system. The proposed design of hybrid circuit breaker (HCB) involves combination of mechanical and electronic switches for efficient fault interruption. The mechanical part is covered by using vacuum circuit breaker (VCB) and the electronic switching part involves use of SiC-MESFET as these are more powerful and fast switching elements. For the fault interruption schemes to be valid, artificial current zero is created using current commutation. The system model is designed using Simulink and comparisons are carried out between the proposed hybrid scheme and the recent fault interruption schemes in terms of power loss and fault clearing time. The results of the proposed design are measured in terms of system current, commutation current and voltage across the commutation capacitor.